Seasonal Changes in Hemolymph Protein Level and Hypopharyngeal Gland Size Depending on Age and In-Nest Location of Honeybee Workers - Musila, Jan; Přidal, Antonín (Animals, 2024)
A honeybee colony, as a super-organism, is regulated through age-polyethism. A honeybee worker's age is considered by means of a chronological and biological approach. The biological age is estimated with physiologically related biological markers, e.g., total hemolymph protein content (THP) and hypopharyngeal gland size (HGs), which also vary seasonally. Contemporary insights into the age-related spatial workers' distribution within the hive nest space regarding biological age are insufficiently clarified. This study aimed to monitor changes in selected physiological markers during the entire season in relation to worker age and their spatial position in the hive nest. THP content and HG size analysis was performed in nine colonies for the entire season to compare the physiological markers within and among the groups of the workers whose ages were known and sampled in different hive parts. Seasonal impact on the biomarkers' development was confirmed in known-age workers. In the case of HGs, this impact was the most apparent in 4- and 5-week-old workers. For THP, the seasonal impact was the most obvious in 2-week-old workers. The highest THP was found in 1- and 2-week-old workers during the entire season. Biologically younger workers of the same age were located predominantly in upper hive parts consistently throughout the year and vice versa. These workers showed significantly higher THP in comparison with those sampled below. Regarding the chronological age, the downwards, spatially shifting mechanism of workers within the hive nest while they aged was characterized. We recommend storage of diluted hemolymph samples up to one month before performing an assay if necessary. The physiological context, relation to division of labor and benefits for beekeeping practices are discussed.
Keywords: worker; physiology; distribution; sample; biomarkers; age-polyethism; Apis mellifera